Literatur Review: Dampak Implementasi Electronic Health Records (EHR) di Pelayanan Kesehatan - Tria Saras Pertiwi; Adi Supryatno (Universitas Banten Jaya, 2023)
Document management using electronic/computer-based systems in the scope of health services is becoming a global trend, one of which is Electronic Health Records (Electronic Health Records or EHR). The purpose of this study was to determine the impact of implementing Electronic Health Records in health services. The method used is Literature Review from databases originating from PubMed and ScienceDirect. After the articles were screened, 15 articles were selected to be used as a Literature Review. The results of a review based on 15 articles show that the impact of implementing Electronic Health Records in health services is obtained from various aspects including aspects of efficiency, communication, workload, quality and accuracy of data, economy, quality of care for patients. All articles show different results. There is an increasing impact in a positive direction, but there are some negative impacts such as workload, communication, and dysfunctional workflow. There were also findings of perceived barriers to EHR use, for example poor training and lack of user knowledge.